MOTIVASI BELAJAR DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN ISLAM - Ismail Syakban; Julhadi Julhadi; Nurmisbah Nurmisbah; Yetnita Yetnita (STKIP Pesisir Selatan, 2026)
Learning motivation is one of the important factors that determines students’ success in the educational process. This study aims to examine learning motivation from the perspective of Islamic educational psychology, including the definition, types of motivation, theories of learning motivation, factors influencing learning motivation, and strategies to improve students’ learning motivation. This research uses a library research method with a qualitative descriptive approach. The results of the study indicate that learning motivation plays an important role in encouraging, directing, and maintaining students’ learning activities. In the Islamic perspective, learning motivation is not only oriented toward academic achievement but also has a spiritual dimension as a form of worship to Allah SWT. Therefore, the integration of psychological motivation and Islamic values is highly necessary to create an effective and meaningful learning process.